Scheduling Critical Activities on Multi-objectives Stochastic Projects - Salman, Saad Mohsin (Al-Nahrain Journal of Science, 2018)
In this paper, we consider the problem of stochastic multi-objectives project when some or all activities are interrupted and are on different allocations (i.e. are independent on each other). Some theories concerning multi-objectives problems are presented, and a new objective function is constructed). An approach has been built to schedule the critical activities, by constructing some expressions based on the project lateness costs due to the interruption activities, to obtain the corresponding critical cost index. A simple tested problem is presented.